Effect of carbohydrate ingestion on ratings of perceived exertion during a marathon - Utter, A. C.; Kang, J.; Robertson, R. J.; Nieman, D. C.; Chaloupka, E. C.; Suminski, R. R.; Piccinni, C. R. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: The purpose of this study was to investigate the effects of carbohydrate substrate availability on ratings of perceived exertion (RPE) and hormonal regulation during a competitive marathon. METHODS: A randomized, double-blind study design was used in which subjects ran the marathon, and every 3.2 km, RPE and heart rate were measured. The marathoners were randomly assigned to receive carbohydrate (C) (N = 48) or placebo (P) (N = 50) beverages at a rate of 1 L x h(-1) during the race. RESULTS: Heart rate (%(HRMAX) ) was lower in P (82.0% +/- 0.6) than C (84.2% +/- 0.6) (P < 0.01), especially during the final 10 km: (78.7% +/- 1.0) and (84.5% +/- 0.7), respectively (P < 0.001). RPE was not significantly different between P and C throughout the marathon (P = 0.08) or during the final 10 km: (16.8 +/- 0.3) and (16.1 +/- 0.3), respectively (P = 0.06). Postrace plasma glucose (P < 0.001), insulin (P < 0.001), and lactate (P < 0.05) levels were significantly lower in P than C, and postrace cortisol (P < 0.05) significantly higher in P compared with C. CONCLUSIONS: Marathoners ingesting carbohydrate compared with placebo beverages were able to run at a higher intensity while reporting a nonsignificant difference in RPEs during a competitive race.